Numerical stress analysis in functionally graded materials - Yong, Soi Choy. (2008)
The present project mainly examines some aspects of the application and development of the boundary element methods for the numerical computation of the displacement and stress fields in functionally graded solids under antiplane elastostatic deformations. Two boundary element approaches are described for functionally graded materials with shear moduli that vary continuously in space.